Addressing the tumour microenvironment in early drug discovery: a strategy to overcome drug resistance and identify novel targets for cancer therapy. Issue 3 (March 2021) - Kaemmerer, Elke; Loessner, Daniela; Avery, Vicky M.
Highlights: Changes in the microenvironment (TME) promote drug resistance. Cellular composition, biochemical and -biophysical parameters create tissue-specific TME. Targeting cancer cell – TME interactions as a strategy to overcome drug resistance. Modelling the TME and TME changes is essential for early drug discovery assays. Challenges of 3D in vitro tumour models with increased complexity. Abstract : The tumour microenvironment (TME) comprises not only malignant and non-malignant cells, but also the extracellular matrix (ECM), secreted factors, and regulators of cellular functions. In addition to genetic alterations, changes of the biochemical/biophysical properties or cellular composition of the TME have been implicated in drug resistance. Here, we review the composition of the ECM and different elements of the TME contributing to drug resistance, including soluble factors, hypoxia, extracellular acidity, and cell adhesion properties. We discuss selected approaches for modelling the TME, current progress, and their use in low-and high-throughput assays for preclinical studies. Lastly, we summarise the status quo of advanced 3D cancer models compatible with high-throughput screening (HTS), the technical practicalities and challenges. Teaser: The tumour microenvironment, and changes thereof, are key aspects in mediating drug resistance. Capturing these factors in representative, disease-specific in vitro models in early drug discovery efforts would improve drug discovery outcomes; however, to date, this remains challenging.